2018
DOI: 10.1101/498436
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parallel genomic evolution of parasite tolerance in wild honey bee populations

Abstract: Sudden biotic pressures, such as those from novel diseases and pathogens, require populations to respond rapidly or face potential extinction. How this response process takes 25 place remains poorly understood, particularly in natural environments. In this study we take advantage of unique decade-long data sets of two wild honey bee (Apis mellifera) populations in the United States to reconstruct the evolution of tolerance to a novel parasite, the ectoparasitic mite Varroa destructor. Upon the arrival of Varro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 35 publications
(54 reference statements)
0
17
0
Order By: Relevance
“…Since 1990, AHBs have spread to ten states in the southern US states: Arizona, Arkansas, California, Florida, Louisiana, Oklahoma, Nevada, New Mexico, Texas, and Utah. Their spread, unlike that of the subspecies described above, has largely been accomplished by natural swarming and not beekeeping (Bozek et al 2018;Cridland et al 2018;Pinto et al 2004).…”
Section: Cyprus (Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Since 1990, AHBs have spread to ten states in the southern US states: Arizona, Arkansas, California, Florida, Louisiana, Oklahoma, Nevada, New Mexico, Texas, and Utah. Their spread, unlike that of the subspecies described above, has largely been accomplished by natural swarming and not beekeeping (Bozek et al 2018;Cridland et al 2018;Pinto et al 2004).…”
Section: Cyprus (Tablementioning
confidence: 99%
“…Understanding honey bee genetics and population structure is vital to understanding and maintaining genetic diversity (Bohling et al 2016;Brito et al 2017;Harpur et al 2012Harpur et al , 2015, discovering loci contributing variation to desirable traits (Bolormaa et al 2017;Harpur et al 2019), and ultimately developing breeding programs (Dekkers 2012;Jarquín et al 2014). Fortunately, the USA has a detailed archival record (Crane 1999;Horn 2005;Oertel 1976a, b, c, d, e;Pellett 1938;Sheppard 1989a, b) and there is a growing number of genetic analyses of honey bee populations (Bozek et al 2018;Calfee et al 2020;Cleary et al 2018;Coulson et al 2005;Cridland et al 2018;Darger 2013;Delaney et al 2009;Kono and Kohn 2015;Magnus et al 2011Magnus et al , 2014Magnus and Szalanski 2010;Mikheyev et al 2015;Pinto et al 2004Pinto et al , 2007Rangel et al 2016Rangel et al , 2020Schiff and Sheppard 1993, 1995Schiff et al 1994;Seeley et al 2015;Szalanski et al 2016a, b;Szalanski and Magnus 2010). Here, we synthesize and review historic records (Table S1, S2) and available genetic data sets (Table S3) to understand how management practices have influenced genetic diversity and differentiation of honey bee populations across the United...…”
Section: Introductionmentioning
confidence: 99%
“…While the key genes remain unknown, scutellata -European hybrid honey bees diverge from European-ancestry bees on a number of traits that may have given them a selective advantage during the invasion: they have higher reproductive rates (including faster development times, proportionally higher investment in drone production and more frequent swarming to found new colonies [ 12 ]), they have higher tolerances to several common pesticides [ 40 ], and they prove less susceptible to Varroa mites, a major parasite [ 41 45 ]. Population monitoring studies show that Varroa mites are a strong selective force in the wild and that mite infestations in the 1990s likely contributed to the rapid genetic turnover of feral nest sites from European to scutellata -European hybrid colonies in Arizona and Texas [ 28 , 29 , 36 ]. European ancestry may have also contributed to the success of the invasion; a recent study of scutellata -European hybrid bees in Brazil revealed some European alleles at exceptionally high frequency, but this work was under-powered to detect high-fitness scutellata alleles due to elevated genome-wide scutellata ancestry (84%) in the Brazilian population [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous genomic work on the invasion has shown that scutellata-European hybrid honey bees are a genetic mixture of three major genetic groups: A from Africa, C from eastern Europe and M from western Europe [32][33][34][35][36][37]. Historical sources indicate that the A ancestry is from A. m. scutellata [38,39], while both M and C ancestries are mixtures of multiple subspecies imported from Europe, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…While the key genes remain unknown, scutellata-European hybrid honey bees diverge from European-ancestry bees on a number of traits that may have given them a selective advantage during the invasion: they have higher reproductive rates (including faster development times, proportionally higher investment in drone production and more frequent swarming to found new colonies [12]), they have higher tolerances to several common pesticides [40], and they prove less susceptible to Varroa mites, a major parasite [41][42][43][44][45]. Population monitoring studies show that Varroa mites are a strong selective force in the wild and that mite infestations in the 1990s likely contributed to the rapid genetic turnover of feral nest sites from European to scutellata-European hybrid colonies in Arizona and Texas [28,29,36]. European ancestry may have also contributed to the success of the invasion; a recent study of scutellata-European hybrid bees in Brazil revealed some European alleles at exceptionally high frequency, but this work was under-powered to detect high-fitness scutellata alleles due to elevated genome-wide scutellata ancestry (84%) in the Brazilian population [37].…”
Section: Introductionmentioning
confidence: 99%